The Influence of Behavioral Factors in Making Investment Decisions and Performance: Study on Investors of Colombo Stock Exchange, Sri Lanka - Kengatharan, L.; Kengatharan, N. (Asian Journal of Finance & Accounting, 2014)
The main objective of this study is exploring the behavioral factors influencing individual investors’ decisions at the Colombo Stock Exchange. Furthermore, the relations between these factors and investment performance are also examined. As there are limited studies about behavioral finance in Sri Lanka, this study is expected to contribute significantly to the development of this field in Sri Lanka. The study begins with the existing theories in behavioral finance, based on which, hypotheses are proposed. Then, these hypotheses are tested through the questionnaires distributed to individual investors at the Colombo Stock Exchange. The collected data are analyzed by using SPSS. The result shows that there are four behavioral factors affecting the investment decisions of individual investors at the Colombo Stock Exchange which are Herding, Heuristics, Prospect and Market. Most of the variables from all factors have moderate impacts whereas anchoring variable from heuristic factor has high influence and choice of stock variable from herding factor has low influence on investment decision. This study also tries to find out the influence of behavioral factors on investment performance. Among the behavioral factors mentioned above, only three variables are found to influence the investment performance: choice of stock has negative influence which is from herding factor. Over confidence from heuristics factor has negative influence on investment performance. Anchoring from heuristics factor has positive influence on investment performance. All other variables which are volume of stock, buying and selling and speed of herding variables of herding factor, loss aversion and regret aversion variables of prospect factor and market information and customer preference variables of market factor do not have influence on investment performance.
Keywords: Behavioral finance